Philosophical Enterprise and the Scientific Spirit - Manickam, Thomas (Journal of Dharma, 1996)
G.C.Nayak, Philosophical Enterprise and the Scientific Spirit. Delhi : Ajanta Publications, (1994), pp,xii + 160, Rs. 195/- SBN-81 - 2020405-0.